Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5852/cr-palevol2021v20a44
|View full text |Cite
|
Sign up to set email alerts
|

The end of the Ice Age in southern Europe: Iberian images in the Palaeolithic to Post-Palaeolithic transition

Abstract: The documentation of Palaeolithic art in the open air, together with direct dates for parietal art and the study of territories marked by the last hunter groups in southern Europe, supports new interpretations of Palaeolithic art and its continuity in the early Holocene. We provide updated information about the graphic representations in that time of transition, grouped under the term Style V. We also reflect on the chronological framework of some themes and techniques for which dates are available, from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…The oldest dates, related to a pig depiction in Leang Tedongnge cave, offer a date older than 45,000 years. In Leang Balangajia cave the estimate is younger than 73,000 years (Aubert et al 2014;2019;Brumm et al 2021). Similar results have been obtained at six sites in Borneo, using the U/Th dating system; dates are older than 40,000 years for an animal painting and younger than 51,000 years for a hand stencil in the same panel in Lubang Jeriji Saléh cave in Borneo, always separated from Sulawesi by a significant sea-crossing (Aubert et al 2018b).…”
Section: Pleistocene Rock Art and Essentialismsupporting
confidence: 78%
See 2 more Smart Citations
“…The oldest dates, related to a pig depiction in Leang Tedongnge cave, offer a date older than 45,000 years. In Leang Balangajia cave the estimate is younger than 73,000 years (Aubert et al 2014;2019;Brumm et al 2021). Similar results have been obtained at six sites in Borneo, using the U/Th dating system; dates are older than 40,000 years for an animal painting and younger than 51,000 years for a hand stencil in the same panel in Lubang Jeriji Saléh cave in Borneo, always separated from Sulawesi by a significant sea-crossing (Aubert et al 2018b).…”
Section: Pleistocene Rock Art and Essentialismsupporting
confidence: 78%
“…In our view, recent research has reinforced the biological coupling of rock art with a privileged set of cognitive abilities, rather than expanding the array of potential explanations of this cultural practice. We will focus on two examples: the debate around Neanderthal authorship of rock-art depictions in different caves in Spain (Hoffman et al 2018a;White et al 2019), and the recently published ancient rock art found in Southeast Asia (Brumm et al 2021;Taçon et al 2014).…”
Section: Pleistocene Rock Art and Essentialismmentioning
confidence: 99%
See 1 more Smart Citation
“…Por ello, la generalización de estos formalismos «esquematizantes» en las evidencias gráficas datadas en torno al 13500 cal BP en contextos mobiliares y parietales, sumada a la coexistencia de estos con otros de carácter naturalista en algunas representaciones (a lo que podemos añadir, además, la ausencia de indicadores técnicos claros en el caso particular de Arenaza), hace que optemos por descartar que los en Francia (por ejemplo, Abri Morin -Paillet y Man Estier, 2014-), así como en el interior peninsular (por ejemplo, Fari seu -García-Díez y Aubry, 2002-y Esteban vela -Gar cía-Díez, 2013-) y el ámbito mediterráneo (por ejemplo, Molí del Salt - García-Díez et alii, 2002-o Matutano -Olària, 19992008-), seña lando una generalización y expansión geográfica de este modelo de representación figurativa que ha impulsado a la definición formal de un Estilo V dotado de un alcance sud-europeo (Bueno et alii, 2009(Bueno et alii, , 2022Bueno y Balbín, 2021).…”
Section: Dinámicas De Representación Zoomorfa En El Grafismo Finipale...unclassified